Is SARS-CoV-2 Vertically Transmitted? - Simões e Silva, Ana Cristina; Leal, Caio Ribeiro Vieira (Frontiers in Pediatrics, 2020)
At the end of 2019, in Wuhan (China), the onset of a pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was observed. The disease, named as COVID-19, has a wide spectrum of clinical presentation. Apparently, being a child or being pregnant does not represent an additional risk for adverse outcomes. The purpose of this mini-review was to investigate what is in the scientific literature in regard to vertical transmission of SARS-CoV-2. Data were obtained independently by the two authors who carried out a systematic search in the PubMed, Embase, LILACS, Cochrane, Scopus and SciELO databases using Medical Subject Heading terms as "coronavirus", "COVID-19" and "vertical transmission". There are few studies about the vertical transmission of SARS-CoV-2. In all case reports and case series, the mothers’ infection occurred in the third trimester of pregnancy, there was no maternal deaths and most neonates had favorable clinical course. The virus was not detected in the neonate nasopharyngeal swab samples at birth, in the placenta, in the umbilical cord, in the amniotic fluid, in the breast milk or in the maternal vaginal swab in any article. Only three papers reported neonatal SARS-CoV-2 infection, but there is a bias that positive pharyngeal swab samples were collected at 36 hours and on the 2nd, 4th and 17th day of life. The possibility of intrauterine infection has been based mainly on the detection of IgM and IL-6 in the neonates' serum. Up to now, no convincing evidence was found for vertical transmission to COVID-19.